Control of fetal membrane prostaglandin E2 production by bacteria. - Helmig,R; Roseblade,CK; Uldbjerg,N; Elder,MG; Sullivan,MH (Acta Obstet Gynecol Scand, 1990)
The effect of bacteria on the production of prostaglandin E2 (PGE2) and PGE2 metabolites by fetal membranes has been investigated. Live bacteria stimulated a large increase in the levels of PGE2 metabolites, but only a small increase in the levels of PGE2 on the fetal side of the membranes. No significant changes in the levels of PGE2 or its metabolites were found on the maternal side. Bacteria may therefore stimulate PGE2 production by fetal membranes during short-term incubations, but it seems that the metabolic capacity of the chorion was so high that no change in PGE2 levels was detectable on the maternal side of the fetal membranes. This was confirmed by the finding that less than 1% of 3H-PGE2 added to the fetal side of the membrane reached the maternal side without being metabolized.